Аbout role perspective in the strategy of future-teachers-philologists’ pedagogical training quality raising (Pedagogy of Higher and Secondary Education, 2012)
Yablonckaya T. Аbout role perspective in the strategy of future-teachers-philologists’ pedagogical training quality raising.The theoretical ground of the role perspective as the main idea of the strategy of future teachers-philologists’ pedagogical training quality raising, its essence and the ways of realization in the teachingprocess are discovered.
Keywords: role perspective; the strategy of pedagogical training quality raising; role situation